THE ECONOMIC EFFICIENCY OF GEOTHERMAL HEATING SYSTEM IN SMALL-SCALE GREENHOUSE OPERATIONS IN BOSNIA AND HERZEGOVINA - Bećirović, Emir; Čadro, Sabrija; Makaš, Merima; Zahirović Sinanović, Ćerima; Omerović, Zuhdija (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Greenhouse vegetable production offers many advantages over traditional open-field cultivation methods. These benefits include regulating and controlling growing conditions, leading to higher crop yields, year-round production, and increased resource allocation efficiency. Many studies demonstrate that heating systems improve production in greenhouses, leading to increased yields and improved economic profitability. However, similar research is lacking in Bosnia and Herzegovina, particularly in regions with a continental climate. Therefore, the main goal of this study was to evaluate the economic efficiency of vegetable production (lettuce, spring onion, tomato, and spinach)  in a greenhouse equipped with an additional heating system compared to one without such a system. The experiment was conducted in two 100 m2 greenhouses using identical cultivation technology. The results showed that the temperature in the two separate greenhouses was statistically significantly different in winter; however, the observed yields did not show a statistically significant difference. Unexpectedly, the economic results were contrary to expectations, with lower returns in the greenhouse with heating. The main reason is the higher costs associated with deprecation (1,238 BAM) and the geothermal pump's electricity consumption (700 BAM). In conclusion,  through this research, it was found that the tested vegetable production using a geothermal heat pump is not economically justified. It is recommended to consider the use of such equipment under different conditions, such as larger greenhouse areas with improved insulation (double-layered plastic). Furthermore, it is recommended that similar experiments be conducted at this location to confirm or challenge the results obtained in this study.